Dissection of Ras-Dependent Signaling Pathways Controlling Aggressive Tumor Growth of Human Fibrosarcoma Cells: Evidence for a Potential Novel Pathway - Gupta, Swati (American Society for Microbiology, 2000)
Activation of multiple signaling pathways is required to trigger the full spectrum of in vitro and in vivo phenotypic traits associated with neoplastic transformation by oncogenic Ras. To determine which of these pathways are important for N-ras tumorigenesis in human cancer cells and also to investigate the possibility of cross talk among the pathways, we have utilized a human fibrosarcoma cell line (HT1080), which contains an endogenous mutated allele of the N-ras gene, and its derivative (MCH603c8), which lacks the mutant N-ras allele. We have stably transfected MCH603c8 and HT1080 cells with activating or dominant-negative mutant cDNAs, respectively, of various components of the Raf, Rac, and RhoA pathways. In previous studies with these cell lines we showed that loss of mutant Ras function results in dramatic changes in the in vitro phenotypic traits and conversion to a weakly tumorigenic phenotype in vivo. We report here that only overexpression of activated MEK contributed significantly to the conversion of MCH603c8 cells to an aggressive tumorigenic phenotype. Furthermore, we have demonstrated that blocking the constitutive activation of the Raf-MEK, Rac, or RhoA pathway alone is not sufficient to block the aggressive tumorigenic phenotype of HT1080, despite affecting a number of in vitro-transformed phenotypic traits. We have also demonstrated the possibility of bidirectional cross talk between the Raf-MEK-ERK pathway and the Rac-JNK or RhoA pathway. Finally, overexpression of activated MEK in MCH603c8 cells appears to result in the activation of an as-yet-unidentified target(s) that is critical for the aggressive tumorigenic phenotype.